Language learning motivation: what's on a student's mind when learning English language - Ahmed, Tahreen (BRAC University, 2010)
This paper explores students' language learning motivation and the factors that motivate and demotivate them in English learning at BRAC University. A total of 124 ENG-091 students were surveyed in summer 2009 and asked about their reasons for learning English, whether they felt motivated in attending their classes and the factors that motivate and demotivate them. Also suggestions are given on how ENG-091 can be developed further so that students feel intrinsically motivated to learn language for their own sake rather than for external rewards such as grades and a good job as the findings suggest.